1995
DOI: 10.1117/12.205993
|View full text |Cite
|
Sign up to set email alerts
|

<title>Computer tomographic (CT) image reconstruction from limited information</title>

Abstract: A new reconstruction algorithm is introduced to obtain high quality computerized tomography image from limited information.There are many practical cases that only limited projection data can be collected due to the physical constraints of hardware system and the object structure. In these cases , conventional reconstruction algorithms which require complete projections are often unacceptable because it causes severe streak artifacts and distortions. So image reconstruction from limited information is very imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It is important to note that, this time, the verification has gone through the testing with projection data acquired by clinical MDCT. Both HLCC (Natterer 1986, Li and Wang 1995, Basu and Bresler 2000, Wang and Sze 2001, Clackdoyle 2013, Clackdoyle and Desbat 2015 and DIIC (Wei et al 2006, Tang et al 2012 are data consistency constraints, but they are established under parallel beam geometry and fan beam geometry, respectively. The primary advantage of DIIC over HLCC lies in the fact that the former only requires the engagement of one pair of projection views acquired at any angle under the fan beam geometry, whereas the latter demands the engagement of a large number of neighboring projection views acquired at relatively high and uniform sampling rate in the angulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that, this time, the verification has gone through the testing with projection data acquired by clinical MDCT. Both HLCC (Natterer 1986, Li and Wang 1995, Basu and Bresler 2000, Wang and Sze 2001, Clackdoyle 2013, Clackdoyle and Desbat 2015 and DIIC (Wei et al 2006, Tang et al 2012 are data consistency constraints, but they are established under parallel beam geometry and fan beam geometry, respectively. The primary advantage of DIIC over HLCC lies in the fact that the former only requires the engagement of one pair of projection views acquired at any angle under the fan beam geometry, whereas the latter demands the engagement of a large number of neighboring projection views acquired at relatively high and uniform sampling rate in the angulation.…”
Section: Discussionmentioning
confidence: 99%
“…A quadratic objective function based on the HLCC has been defined in Tang et al (2011) to determine the scaling factor λ 0 that is optimal for equation (9). However, the HLCC, either in its original form defined under parallel beam geometry (Natterer 1986, Li and Wang 1995, Basu and Bresler 2000, Wang and Sze 2001, Clackdoyle 2013, Clackdoyle and Desbat 2015 or its derivative under fan beam geometry (Yu et al 2006, Yu and Wang 2007, Tang et al 2011 demands the engagement of a large number of neighboring projection views and thus limits it applications over situations where projection data can only be acquired at sparse or non-uniform angular sampling rate. To address this drawback, we propose a method based on DIIC (Wei et al 2006, Tang et al 2012.…”
Section: Data Integral Invariant Constraintmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Meanwhile, the projection data consistency conditions have been utilized to solve several XCT problems. [30][31][32][33][34][35][36][37][38][39] Particularly, it was demonstrated that the beam-hardening correction based on the physical model of x ray imaging, and the H-L consistency condition, is feasible. 25 Inspired by previous investigations, in this article we will construct an objective function by combining the bone-correction formula with the H-L consistency condition, and optimize the objective function to automatically and stably determine the scaling factor and corresponding coefficient vector for beam hardening correction in polychromatic XCT imaging.…”
Section: Introductionmentioning
confidence: 99%